2011
DOI: 10.1007/s10712-011-9155-x
|View full text |Cite
|
Sign up to set email alerts
|

Depth-Recursive Tomography of the Bohemian Massif at the CEL09 Transect—Part B: Interpretation

Abstract: In the accompanying paper (Part A), depth-recursive tomography was applied to the CEL09 refraction data. A deblurred P-wave velocity image was obtained down to a depth of 20 km. This paper (Part B) is devoted to the interpretation of the upper-and middle-crustal structures of the Bohemian Massif imaged in the CEL09 section. Because of inherent ambiguity of the refraction method in imaging low-velocity zones, other wellknown results based on other geophysical data sets are also used to independently verify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…We will be perform such extended comparison with the 9HR density model derived by Š vancara and Chlupáčová (1997)-see fig. 4 in Part B (Novotný 2012). It will be shown that the 6,100 ms -1 isovelocity of the DRTG image tightly correlates with the density interface of mafic intrusion in a length over 50 km.…”
Section: Comparison With Previous Tomographic Resultsmentioning
confidence: 84%
“…We will be perform such extended comparison with the 9HR density model derived by Š vancara and Chlupáčová (1997)-see fig. 4 in Part B (Novotný 2012). It will be shown that the 6,100 ms -1 isovelocity of the DRTG image tightly correlates with the density interface of mafic intrusion in a length over 50 km.…”
Section: Comparison With Previous Tomographic Resultsmentioning
confidence: 84%
“…If it exaggerates the travel-time residuals after tomo- Fig. 12 The P-wave velocities and Bouguer anomalies along the CEL09 profile (Novotný 2012). The model fits the travel times at the marked grid nodes with an overall RMS of 97 ms (Novotný 2011).…”
Section: Interpreting the Velocity Patternsmentioning
confidence: 98%
“…The derived velocity image revealed the subduction features which remained previously unresolved by the ray-tracing modeling of Hrubcová et al (2005) and also by the non-iterative method of Růžek et al (2007). The CEL09 velocity section particularly imaged the mafic intrusions shaped by the inclined slab of Saxothuringian crust subducted beneath the TBU (Novotný 2012).…”
Section: Previous Seismic Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This Přibyslav-Vitice fault zone represents NNE-SSW sinistral strike-slip fault marked by a zone of mylonitization [8]. It represents very important seismic zone [3] and geophysical boundary [5].…”
Section: Introduction mentioning
confidence: 99%